Idiopathic aplastic anemia: a rare case report in Jammu and Kashmir region, India - Sharma, Smriti; ., Upma; Mani, Deep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Idiopathic aplastic anemia is a pancytopenia disorder that is a rare but life threatening for both mother and fetus during pregnancy. Association of aplastic anemia with pregnancy is unclear but considered to be interrelated. Bone marrow transplantation is the most effective treatment for adult aplastic anemia but is inadvisable to perform during pregnancy because of the teratogenic effect of immunosuppressive agents or radiation therapy to the growing fetus. Supportive care, withdrawal from offending drugs and involving erythrocytes and platelets transfusion is a promising way to save the life. Here author present a case report of 36-year-old lady with idiopathy aplastic anemia. In this case medical investigation revealed severe anemia of unknown origin. The patient was treated with hematinics, blood transfusion and glucocorticoids. A healthy baby was delivered without evidence of hemolysis at her eight month and one week of pregnancy, the patient recovered and discharged with normal incidence. Being a rare case, it becomes a necessity to report such life-threatening disorder and management. Moreover, to our knowledge this is the first case reported of its kind from Jammu and Kashmir Division of India.